Intervention Effects of a Kindergarten-Based Health Promotion Programme on Motor Abilities in Early Childhood - Kobel, Susanne; Henle, Lea; Laemmle, Christine; Wartha, Olivia; Szagun, Bertram; Steinacker, Juergen Michael (Frontiers in Public Health, 2020)
Background: Physical activity is positively related to motor abilities. Especially in childhood, an active lifestyle is important to support healthy motor development. The low-threshold health promotion programme „Join the Healthy Boat“ in kindergartens promotes physical activity in order to also improve motor abilities. Here, effects of the programme on children’s motor abilities after one year were investigated. Materials and methods: The longitudinal study included 419 children (3.7 ± 0.6 years) from 58 kindergartens throughout south-west Germany (intervention: 254, control: 165). Children in the intervention group received physical activity promotion with a focus on motor ability development, led by teachers, through one kindergarten year; children in the control group followed the normal kindergarten routine. At baseline and follow-up, motor tests (3-min-run, one-leg-stand, standing long jump, sit-and-reach-test) were performed, anthropometric measures (body weight and height) were taken and a parental questionnaire was issued. Intervention effects were assessed using differential measures (follow-up – baseline) adjusted for gender, age, socioeconomic status (SES) and baseline values, with covariance analyses. Results: Children in the intervention group showed a significant improvement in endurance performance (F(1.329)= 20.95,p< .000,η_P^2=0.060), which applies to boys (F(1,172)= 13,66,p≤ .000,η_P^2=0,074) and girls (F(1,152)= 7,48,p≤ .007,η_P^2=0,047). No significant intervention effects on endurance performance were found for children with low baseline values, children with a low SES, and children aged five years, nor for any other assessed motor ability. Conclusions: The theory-based, teacher-centred intervention promoting physical activity in order to also improve motor abilities has shown a positive effect on endurance performance in kindergarten children, but no other motor ability. Future interventions should therefore be either longer, more intense and take into account children’s age, initial level of performance and their SES. In addition, the influence of teachers should be considered more closely in future research.